Emerging roles of mitochondrial sirtuin SIRT5 in succinylation modification and cancer development - Zhangmin Ke; Zhangmin Ke; Kaikai Shen; Li Wang; Hao Xu; Xia Pan; Zhenjue Qian; Yuting Wen; Tangfeng Lv; Xiuwei Zhang; Yong Song (Frontiers in Immunology)
Succinylation represents an emerging class of post-translational modifications (PTMs), characterized by the enzymatic or non-enzymatic transfer of a negatively charged four-carbon succinyl group to the ϵ-amino group of lysine residues, mediated by succinyl-coenzyme A. Recent studies have highlighted the involvement of succinylation in various diseases, particularly cancer progression. Sirtuin 5 (SIRT5), a member of the sirtuin family, has been extensively studied for its robust desuccinylase activity, alongside its deacetylase function. To date, only a limited number of SIRT5 substrates have been identified. These substrates mediate diverse physiological processes such as glucose oxidation, fatty acid oxidation, ammonia detoxification, reactive oxygen species scavenging, anti-apoptosis, and inflammatory responses. The regulation of these activities can occur through either the same enzymatic activity acting on different substrates or distinct enzymatic activities targeting the same substrate. Aberrant expression of SIRT5 has been closely linked to tumorigenesis and disease progression; however, its role remains controversial. SIRT5 exhibits dual functionalities: it can promote tumor proliferation, metastasis, drug resistance, and metabolic reprogramming, thereby acting as an oncogene; conversely, it can also inhibit tumor cell growth and induce apoptosis, functioning as a tumor suppressor gene. This review aims to provide a comprehensive overview of the current research status of SIRT5. We discuss its structural characteristics and regulatory mechanisms, compare its functions with other sirtuin family members, and elucidate the mechanisms regulating SIRT5 activity. Specifically, we focus on the role of succinylation modification mediated by SIRT5 in tumor progression, highlighting how desuccinylation by SIRT5 modulates tumor development and delineating the underlying mechanisms involved.